Evaluation of missing-tooth effect on articular eminence inclination of temporomandibular joint - Meng-Ta Chiang; Tsung-I Li; Hsiao-Wen Yeh; Chi-Chun Su; Kuo-Chou Chiu; Ming-Pang Chung; Ren-Yeong Huang; Yi-Shing Shieh (Elsevier, 2015)
Background/purpose: Occlusion is an important component of temporomandibular joint (TMJ). Little is known about the association between missing teeth and TMJ changes. The purpose of this study was to determine if a correlation exists between unilateral missing posterior teeth and changes in the inclination of the articular eminence (AE). Materials and methods: A total of 106 joints in 53 patients (20 men and 33 women) with unilateral posterior edentulism were included. In the same patients, the sagittal outline of the AE and glenoid fossa was traced in panoramic radiographs. The sagittal condylar path inclination was constructed by joining the crest of the glenoid fossa and the crest of AE. This was then related to the constructed Frankfurt's horizontal plane to determine the inclination of AE. The results were subjected to the one-way analysis of variance test. A P value of <0.05 was considered to be statistically significant. Results: In this study 27% of the individuals were right posterior edentulous and 26% were left posterior edentulous. The mean value of AE inclination was 37.7°, ranging from 4° to 58°. A trend showing increased inclination angle in the nonmissing side compared with the missing side was observed (P > 0.05). The inclination of AE in men was higher than in women on both the missing side and the nonmissing side (P > 0.05). The symmetry equality between the missing and the nonmissing side joint was 1.89%. This value was higher (3%) in the female group than in the male group (0%). Comparing the absolute mean differences, the female group showed a lower difference (9.8°) than the male group (12.11°). Conclusion: A wide range of values of AE inclination was found regardless of other factors such as side of teeth loss and the sex of patients.